Leaf morphology and life form influence water relations of Hakea species on different soil substrates within southwestern Australia. - Groom, Philip; Lamont, Byron (1995)
Water relations (xylem pressure potential (XPP), transpiration, stomatal conductance) and leaf specific resistivity (LSR) of four co-occurring Hakea species at each of four sites (two sites on rocky laterite, two sites on deep sand) were investigated under moist spring and summer drought conditions. Hakea species can be classified as possessing broad or terete (needle-like) leaves, and either die or resprout in response to fire. Species representing each of these four morphological groups were examined at all sites. The eight species inhabiting the lateritic sites were more stressed (more negative XPP) in summer than the eight species on sandy soils, with lower conductances and higher LSR in both seasons. Broad-leaved species had higher transpiration rates and LSR, and more negative XPP in both seasons, but lower conductances in spring, than terete-leaved species. Non-sprouters had lower XPP in summer, and lower transpiration rates and conductances in both seasons, than resprouters. Among interaction effects, non-sprouters on lateritic sites had the lowest water relations values in summer (drought tolerators) with no consistent trends in spring. There was a tendency for broad-leaved resprouters on sandy soils to have higher summer water relations values (drought avoiders). Broad-leaved non-sprouters on lateritic soils could be considered the most water stressed group, with substantial plant death during the summer period. Terete-leaved species on sandy soils had the highest XPP in both seasons. Thus the relative ecophysiology of co-occurring species varying in leaf morphology and life form may be site dependent, with differences between morphological groups most prominent during summer.